Six Wishes of a Public Service Librarian. - Kathy Fescemyer (Issues in Science and Technology Librarianship)
This article discusses a librarian's wishes for public service librarianship. The wishes would help the librarian teach concepts about information, databases and earch engines more efficiently and effectively to a large population of library users.